2019
DOI: 10.1002/jcb.28371
|View full text |Cite
|
Sign up to set email alerts
|

SMAD3 inducing the transcription of  STYK1 to promote the EMT process and improve the tolerance of ovarian carcinoma cells to paclitaxel

Abstract: Objective: To figure out the relationship between SMAD3 and serine-threonine tyrosine kinase (STYK1) in ovarian carcinoma cell's paclitaxel resistance. Methods:The quantitative reverse transcription-polymerase chain reactpostion and Western blot analysis were used to analyze RNA and protein content of SMAD3 and STYK1, respectively. The chromatin immunoprecipitation assay was used to confirm the binding site of SMAD3 to the STYK1 promoter region. Transwell assay was used to detect cell invasion and migration, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
(113 reference statements)
0
9
0
Order By: Relevance
“…Apart from TGFβ, other ligands can activate the TGFβ pathway, such as BMP9, a member of the TGFβ superfamily. BMP9 induced platinum resistance by activating EMT in HO8910 and SKOV3 cell lines [113]. Furthermore, tumor-derived TGFβ stimulated TGFβ secretion by mesothelial cells with subsequent phosphorylation of Smad2 and induction of Zeb1.…”
Section: Emt and Chemotherapy Resistancementioning
confidence: 99%
“…Apart from TGFβ, other ligands can activate the TGFβ pathway, such as BMP9, a member of the TGFβ superfamily. BMP9 induced platinum resistance by activating EMT in HO8910 and SKOV3 cell lines [113]. Furthermore, tumor-derived TGFβ stimulated TGFβ secretion by mesothelial cells with subsequent phosphorylation of Smad2 and induction of Zeb1.…”
Section: Emt and Chemotherapy Resistancementioning
confidence: 99%
“…Expression of STYK1 (serine/threonine/tyrosine kinase 1, also known as NOK, a novel oncogene with kinase-domain) is aberrant in many malignancies ( Moriai et al, 2006 ; Jackson et al, 2009 ; Kondoh et al, 2009 ; Orang et al, 2014 ; Chen et al, 2016 , 2017 ; Hu et al, 2018 ). Moreover, overexpressed STYK1 likely stimulates cancer development by sustaining proliferative signaling, leading to abnormal proliferation of cancer cells ( Chung et al, 2009 ; Cao et al, 2016 ; Chen et al, 2016 ), enhancing the resistance of tumor cells to programmed cell death ( Lai et al, 2019 ; Shi et al, 2019 ), promoting the Warburg effect, remodeling cellular energetics in malignant cells ( Shi et al, 2017 ; Zhao et al, 2017 ), and stimulating angiogenesis and lymphangiogenesis during tumor progression ( Liu et al, 2016 ). In addition, a high level of STYK1 downregulates the expression of E-cadherin ( Chen et al, 2005 , 2017 ) and induces EMT via MAPK/ERK and PI3K/AKT signaling ( Chen et al, 2016 , 2017 ; Wang et al, 2016 ), indicating that STYK1 expression correlates with EMT and metastasis, although the precise mechanisms underpinning this relationship need to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…Smad3, as a well-known downstream signal of TGFβ1, can be activated by phosphorylated ALK5 after binding of TGFβ1 to its receptor ( 16 ). Since the TGFβ1/Smad3 signal transduction pathway is involved in inducing EMT in ovarian cancer ( 17 ), we aimed to identify whether the TGFβ1/Smad3 pathway is more activated in 3D-cultured ovarian cancer spheroids than in 2D-cultured ovarian cancer cells. As shown in Figure 1B , higher phosphorylation levels of Smad3 were found in 3D-cultured HEY and A2780 cells than in 2D-cultured cells, which indicated that TGFβ1/Smad3 might play a role in promoting the EMT process in ovarian cancer spheroids.…”
Section: Resultsmentioning
confidence: 99%